2015
DOI: 10.1089/ten.tea.2014.0541
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Rotator Cuff Repair by Sustained Release of Bone Morphogenetic Protein-7 Using a Gelatin Hydrogel Sheet

Abstract: Bone morphogenetic protein-7 (BMP-7) promotes not only osteogenesis but also matrix production in chondrocytes and tenocytes. However, because of its short half-life, maintaining local concentrations of BMP-7 is difficult. We examined the use of a gelatin hydrogel sheet (GHS) for the sustained release of BMP-7 in stimulating rotator cuff repair at the tendon-to-bone insertion. Twelve-week-old male Sprague-Dawley rats were used. Radiolabeled BMP-7 ((125)I-BMP-7) was injected into the subacromial bursa in the (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 45 publications
0
47
0
Order By: Relevance
“…59,73 However, biomechanics were not significantly improved relative to controls. 73 These limited outcomes suggest that additional research will be required to determine whether these chondrogenic/osteogenic BMPs have therapeutic value.…”
Section: Tgf-β Superfamilymentioning
confidence: 84%
See 2 more Smart Citations
“…59,73 However, biomechanics were not significantly improved relative to controls. 73 These limited outcomes suggest that additional research will be required to determine whether these chondrogenic/osteogenic BMPs have therapeutic value.…”
Section: Tgf-β Superfamilymentioning
confidence: 84%
“…Of this group, only BMP2 and BMP7 have been tested in the context of rat rotator cuff healing. Although BMP2 delivery via transduced stem cells dramatically impaired healing (as evidenced by reduced mechanical properties and loss of bone), sustained delivery of BMP7 enhanced fibrocartilage deposition at the tendon‐to‐bone site . However, biomechanics were not significantly improved relative to controls .…”
Section: Biomolecule‐based Therapies For Rotator Cuff Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…In the PDGF‐BB–loaded hydrogel condition, greater collagen fiber orientation, ultimate failure loads, stiffness, and stress to failure were observed at 12 weeks compared with the PBS‐loaded hydrogel control conditions. In another study, Kabuto et al . examined the effect of loading a gelatin hydrogel scaffold with BMP‐7, which is known to promote osteogenesis and matrix production in chondrocytes and tenocytes.…”
Section: Biomaterials For Rotator Cuff Repairmentioning
confidence: 99%
“…In the PDGF-BB-loaded hydrogel condition, greater collagen fiber orientation, ultimate failure loads, stiffness, and stress to failure were observed at 12 weeks compared with the PBS-loaded hydrogel control conditions. In another study, Kabuto et al 108 examined the effect of loading a gelatin hydrogel scaffold with BMP-7, which is known to promote osteogenesis and matrix production in chondrocytes and tenocytes. The BMP-7-loaded hydrogels were augmented, via direct injection, in 12-week-old male Sprague-Dawley rat rotator cuff models, and the results indicated that BMP-7 hydrogel conditions enhanced cartilage matrix production and tendon orientation.…”
Section: Gelatin Hydrogels With Biomoleculesmentioning
confidence: 99%